The Role of Social Relationships in Crowdfunding: A Literature Review on Information, Trust, and Project Funding Success - Habibi Ahmad Syauqi; Farah Qalbia (LPPM STIE Kasih Bangsa, 2024)
This study aims to analyze the impact of social relationships in crowdfunding, focusing on the aspects of information, trust, and project funding. In the context of crowdfunding, social relationships between fundraisers and backers play a significant role in creating an environment that supports project success. The literature review reveals that strong social networks and information transparency can increase the level of backer trust. Trust built through positive social relationships significantly contributes to funding decisions made by individuals. In addition, this study shows that the quality of social relationships can serve as a catalyst in attracting financial support, with a wider network providing access to greater resources. Thus, the results of this study emphasize the importance of fundraisers to build and maintain good social relationships as a strategy to increase the chances of success in crowdfunding. Further research is recommended to explore cultural differences and contexts that may influence the dynamics of social relationships in crowdfunding.